If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -3y = 32 Solving 11 + -3y = 32 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -3y = 32 + -11 Combine like terms: 11 + -11 = 0 0 + -3y = 32 + -11 -3y = 32 + -11 Combine like terms: 32 + -11 = 21 -3y = 21 Divide each side by '-3'. y = -7 Simplifying y = -7
| (3x+2y+y^2)dx+(x+4xy+2x^2)dy=0 | | 3(x+2)-9=28 | | -1+4x=-33 | | 6m+1=25 | | 7(x-2)=12+7x | | -3x+3-7x=53 | | 2k^2-250=0 | | 7x+25=-25 | | 247=x | | 1/9-1 | | x^2+7x=x+16 | | (6m-5)(m+3)=0 | | 6((-5)-9)+4((-5)-6)+23(-5)+9= | | 3x/2-4=6 | | y^5=16y^3 | | 3x+9-2(x+5)=4x-2(3-x) | | (y-9)(y-6)=0 | | 10y-3=-8-4y | | 2x^2=1-5 | | Y=-5+-3X | | (m+1)x=a-1 | | 2(3X+4)-2X=7X-3(-2X+11) | | -6(-1-3x)=96 | | 5/5/6-3/1/3 | | T(n)=100n+5 | | 87(-5)+9(9(-5)-4)= | | -2(8+6x)=-40 | | x^2+38x+3=0 | | (x-3)2+(y-5)2=81 | | 54/9=n/7 | | 21=d | | -105+4(-2(2)+3(-5))+8(2)= |